The influence of individual characteristics on purchase intention for counterfeit products in the fashion industry / Azreen Afiqah Abdul Aziz - Abdul Aziz, Azreen Afiqah (2021)
The world of fashion is full of various variations where it involves the change that keeps pace with current development globally. In general, there are also counterfeit products which had been produced for an income that leads to the occurrence of sales crime cases and endless imitation goods as stated by (Ministry of Domestic Trade and Consumer Affairs, 2021; Research and Market, 2018), where counterfeit products had reached around trillion USD which leads to adversely affecting the fashion industry. As a result, cases of counterfeit goods are getting higher every year until it causes the society to give a novel century, which is The Counterfeiters' Century. The rise of violation has become most popular among customers because they have a high desire to own branded goods, a reputation which involve individual characteristics among customers, especially generation Y (gen - Y) and generation Z (gen - Z). As explained by (Y Pluse, 2020), the most elevated buying power goes to gen - Y with 51% and gen - Z with 53. By that, researcher want to further investigate the individual characteristics susceptibility to normative influence (SN), readiness to take the social risk (RSR) and status acquisition (SA) with purchase intention for counterfeit products (PIC) among gen- Y and gen-Z who are working and had experience on buying counterfeit product. The research strategy of the paper was quantitative data, which measures respondent behaviour, attitude, and intention of counterfeit product for this study. Besides that, the sampling design used non-probability sampling which is convenience sampling. The reason the researcher chooses convenience sampling is because it doesn't have a sample frame, easy and quick to use making it easier for the researcher to reach out to the targeted respondents. The researcher had distributed questionnaires to 510 respondents, to reach out the target respondent 384 respondents. However, only 390 questionnaires were completed and submitted while the rest weren't. The delivery method of the questionnaire was through Google Form and Face-to-Face distribution. The questionnaire had been distributed in Peninsular Malaysia. This investigation was completed with Statistical Packages for Social Science (SPSS) 26.0 versions. The result from this study found that susceptibility to normative influence (SNI) and readiness to take social risk (RSR) were significantly related with the purchase intention for counterfeit products meanwhile status acquisition (SA) shows the opposite result. By that, the researcher recommended that any layer of business team and administration like marketer, policy maker, retailer work together to overcome this issue and problem so that the targeted fashion industry can be reachable.